2007
DOI: 10.28945/394
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service Teachers' Learning Object Development: A Case Study in K-12 Setting

Abstract: Teachers use variety of media to support students' learning. Though there are many new tools and settlements in learning technologies and their specifications, there has been a fierce debate over learning objects and their development. This research aimed to examine the effect of preservice teachers' experience in information and communication technology (ICT) use on their learning object development through (1) inspecting type, number and organization of their learning object (LO) components authored in a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Thus, although Kay, Knaack and Patrarca (2009) noted that WBLRs may be easy and more flexible to use for teaching, mathematics teachers' inability to design their own WBLRs may perhaps, limit the use of these resources in the teaching. The findings in this study support the advocacy in current literature (Akpinar & Simsek, 2007;Nam & Smith-Jackson, 2007;Hadjerrouit, 2010b) for the involvement of teachers in the construction of technology-based learning resources and virtual environments for mathematics education.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Thus, although Kay, Knaack and Patrarca (2009) noted that WBLRs may be easy and more flexible to use for teaching, mathematics teachers' inability to design their own WBLRs may perhaps, limit the use of these resources in the teaching. The findings in this study support the advocacy in current literature (Akpinar & Simsek, 2007;Nam & Smith-Jackson, 2007;Hadjerrouit, 2010b) for the involvement of teachers in the construction of technology-based learning resources and virtual environments for mathematics education.…”
Section: Discussionsupporting
confidence: 77%
“…Approximately 58% and 36% of the web contents met moderate and high pedagogical usability criteria respectively. The low usability rating is not surprising as studies (Akpinar & Simsek, 2007;Hadjerrouit, 2010b) have indicated that some WBLRs created and posted on the internet have considerable pedagogical usability problems. However, key to this study is the finding that approximately 94% of the web modules were found to possess appreciable pedagogical usability characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To realize their potential capabilities, WBLRs need to be designed to support a learner-centered environment, where students explore the content of the subject matter and enhance their learning through interactive, flexible, differentiated, authentic, and motivating activities (John & Sutherland, 2009). Unfortunately, much of the construction of WBLRs is carried out without a true understanding of pedagogy, issues pertinent to learner control, and user involvement (Akpinar & Simsek, 2007;Farrell & Carr, 2007). As a result, current WBLRs provide little support to achieve a high level of flexibility, interactivity, feedback, differentiation, and collaboration, diminishing the added value of WBLRs (Liu & LaMont Johnson, 2005;Martinidale, Cates & Qian, 2005).…”
Section: Development Issuesmentioning
confidence: 99%